THE BASIC ABILITY ON BASIC STATISTICS AND MATHEMATICAL DISPOSITION OF THE SECOND SEMESTER STUDENTS OF MATHEMATICS EDUCATION PGRI UNIVERSITY OF PALEMBANG - Kesumawati, Nila (Prosiding Universitas PGRI Palembang)
AbstractThe objectives of the research are: 1) to know the basic ability of basic statistics and mathematical disposition of the second semester students of  mathematics education in PGRI University of Palembang, (2) is there any significant relationship between the basic ability on basic statistics and mathematical disposition of the second semester students of  mathematics education in PGRI University of Palembang. The methods used in this research are descriptive and correlation methods. The subject of the research are students of mathematics education of PGRI University of Palembang with the total numbered 103 students. The technique of collecting the data are test and questionnaire. Based on the result of data analysis can conclude that (1) the basic ability on basic statistics and mathematical disposition of the second semester students of  mathematics education in PGRI University of Palembang are fair and good. (2) There is no significant relationship between the basic ability on basic statistics and mathematical disposition of the second semester students of  mathematics education in PGRI University of Palembang.Key words: the basic ability on basic statistics, mathematical disposition, descriptive, and correlation